THE ART OF MOVEMENT OF RUDOLF LABAN - do Valle, Flavia Pilla; Sastre, Cibele; Dias Massa, Clóvis (Cena, 2020)
Presentation of articles from issue 32 of the periodical, which addresses topics related to the Art of Movement by Rudolf Laban (1879-1958) and collaborators. This artist and movement researcher produced a legacy for the performing arts from the dance – tone – word triad, resulting from interdisciplinary studies with collaborators from different areas of knowledge such as dance, visual arts, music, theater, psychology, anthropology, theology , education, communication. His work has formed professional generations and Movement Centers that have updated this legacy in several countries for over a century.